Deploying IP and MPLS QoS for Multiservice Networks: Theory and Practice - Evans, John William; Filsfils, Clarence (The Morgan Kaufmann Series in Networking, 2007)
QoS, short for "quality of service," is one of the most important goals a network designer or administrator will have. Ensuring that the network runs at optimal precision with data remaining accurate, traveling fast, and to the correct user are the main objectives of QoS. The various media that fly across the network including voice, video, and data have different idiosyncrasies that try the dimensions of the network. This malleable network architecture poses an always moving potential problem for the network professional.The authors have provided a comprehensive treatise on this subject. They have included topics such as traffic engineering, capacity planning, and admission control. This book provides real world case studies of QoS in multiservice networks. These case studies remove the mystery behind QoS by illustrating the how, what, and why of implementing QoS within networks. Readers will be able to learn from the successes and failures of these actual working designs and configurations. *Helps readers understand concepts of IP QoS by presenting clear descriptions of QoS components, architectures, and protocols*Directs readers in the design and deployment of IP QoS networks through fully explained examples of actual working designs*Contains real life case studies which focus on implementation